2016
DOI: 10.11622/smedj.2016008
|View full text |Cite
|
Sign up to set email alerts
|

Differences in attitudes to end-of-life care among patients, relatives and healthcare professionals

Abstract: INTRODUCTIONThis study explored and compared the differences in attitudes toward end-of-life care among patients, relatives and healthcare professionals, including doctors and nurses. METHODSWe performed a descriptive study on a cross-section of the population of a tertiary hospital in Singapore.Data was collected using a questionnaire survey involving 50 participants from each of the four groups of patients, relatives, doctors and nurses.RESULTS Family members were the most commonly nominated surrogate decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
4
16
0
Order By: Relevance
“…In our study, most individuals nominated their family members to speak on their behalf if they were incapacitated, which is similar to what was observed in other studies (Ang, Zhang, & Lim, 2016). Among healthy and chronically ill patients, the majority did not opt for CPR or other life-sustaining measures.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, most individuals nominated their family members to speak on their behalf if they were incapacitated, which is similar to what was observed in other studies (Ang, Zhang, & Lim, 2016). Among healthy and chronically ill patients, the majority did not opt for CPR or other life-sustaining measures.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies in Singapore have attempted to evaluate the end-of-life treatment decision-making process. A questionnaire conducted on geriatric patients and their relatives, doctors, and nurses by Ang et al found that patients' end-of-life treatment preferences often differed markedly from that of nominated surrogate decisionmakers 13 . A retrospective chart review performed on 683 adult patients who died in hospital without intensive care unit admission concluded that there were infrequent discussions of end-of-life issues with patients, and more work was needed to improve end-of-life care 10 .…”
Section: Discussionmentioning
confidence: 99%
“…The resultant prevailing decision tends to be family-centric rather than patient-centric [8][9][10] . Evidence has shown that surrogate decisionmakers have poor knowledge of CPR and basic resuscitation options, and the decision made by surrogates often differs markedly from patients' own preferences [11][12][13] . Studies in Western populations have shown that only a small proportion of patients and families were knowledgeable about CPR and many overestimated the chances of survival following CPR 11,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Whether more senior physicians have the similar preferences is open for further exploration. Ang et al 16 also describe differences between age groups among Singaporeans regarding regarding end of life care preferences. This study of Singaporeans comprised of mostly young adults and is therefore similar to our study population.…”
Section: Healthcare Professional-related Factorsmentioning
confidence: 99%